The diary of Elizabeth Lee : growing up on Merseyside in the late nineteenth century - Lee, Elizabeth, 1867- (Liverpool University Press, 2010)
Elizabeth Lee grew up on Merseyside in the late nineteenth century. She began her diary at the age of 16 in 1884 and her diary provides an unbroken record of her life up to the age of 25 in 1892. Elizabeth's father was a draper and outfitter with shops in Birkenhead, and throughout the period of the diary Elizabeth lived at home with her family in Prenton. However, she travelled widely on both sides of the Mersey and her diary provides an unusually revealing picture of middle-class life that begins to challenge conventional views of the position of young women in Victorian society.
Keywords: Lee, Elizabeth, -- 1867- -- Diaries.; Merseyside (England) -- History -- 19th century -- Sources.; Merseyside (England) -- Social life and customs -- 19th century -- Sources.; Teenage girls -- England -- Merseyside -- Diaries.; Single women -- England -- Merseyside -- Diaries.; English diaries -- Women authors.; Merseyside (Angleterre) -- Histoire -- 19e siècle -- Sources.; Merseyside (Angleterre) -- Mœurs et coutumes -- 19e siècle -- Sources.; Adolescentes -- Angleterre -- Merseyside -- Journaux intimes.; Femmes seules -- Angleterre -- Merseyside -- Journaux intimes.; English diaries -- Women authors; Manners and customs; Single women; Teenage girls; England -- Merseyside; 1800-1899; Autobiography; Diary; diaries.; autobiographies (literary works); Autobiographies; Diaries; History; Sources; Autobiographies.; Diaries.; Journaux intimes.